Proceedings of the 2018 Conference on Empirical Methods in Natural Language Processing 2018
DOI: 10.18653/v1/d18-1061
|View full text |Cite
|
Sign up to set email alerts
|

Distant Supervision from Disparate Sources for Low-Resource Part-of-Speech Tagging

Abstract: We introduce DSDS: a cross-lingual neural part-of-speech tagger that learns from disparate sources of distant supervision, and realistically scales to hundreds of low-resource languages. The model exploits annotation projection, instance selection, tag dictionaries, morphological lexicons, and distributed representations, all in a uniform framework. The approach is simple, yet surprisingly effective, resulting in a new state of the art without access to any gold annotated data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 22 publications
3
58
0
1
Order By: Relevance
“…Yu et al (2018b) investigated using character-based language models for NER in several languages but did not do any cross-lingual learning. Plank and Agić (2018) used cross-lingual embeddings, projected annotations, and dictionaries for zero-shot cross-lingual part-of-speech tagging.…”
Section: Related Workmentioning
confidence: 99%
“…Yu et al (2018b) investigated using character-based language models for NER in several languages but did not do any cross-lingual learning. Plank and Agić (2018) used cross-lingual embeddings, projected annotations, and dictionaries for zero-shot cross-lingual part-of-speech tagging.…”
Section: Related Workmentioning
confidence: 99%
“…A common challenge in applying natural language processing (NLP) techniques to low-resource languages is the lack of training data in the languages in question. It has been demonstrated that through cross-lingual transfer, it is possible to leverage one or more similar high-resource languages to improve the performance on the low-resource languages in several NLP tasks, including machine score(L tf,1 , L tk ) score (L tf,2 , L tk translation (Zoph et al, 2016;Johnson et al, 2017;Nguyen and Chiang, 2017;Neubig and Hu, 2018), parsing (Täckström et al, 2012;Ammar et al, 2016;Ahmad et al, 2019;, partof-speech or morphological tagging (Täckström et al, 2013;Cotterell and Heigold, 2017;Malaviya et al, 2018;Plank and Agić, 2018), named entity recognition (Zhang et al, 2016;Mayhew et al, 2017;Xie et al, 2018), and entity linking (Tsai and Roth, 2016;Rijhwani et al, 2019). There are many methods for performing this transfer, including joint training (Ammar et al, 2016;Tsai and Roth, 2016;Cotterell and Heigold, 2017;Johnson et al, 2017;Malaviya et al, 2018), annotation projection (Täckström et al, 2012;Täckström et al, 2013;Zhang et al, 2016;Plank and Agić, 2018), fine-tuning (Zoph et al, 2016;Neubig and Hu, 2018), data augmentation (Mayhew et al, 2017), or zero-shot transfer (Ahmad et al, 2019;Xie et al, 2018;Neubig and Hu, 2018;Rijhwani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the multi-source projection experiments, our criteria for filtering is based on whether the sentence was present across all target treebanks and more sophisticated approaches could be used to select better training instances as in Plank and Agić (2018).…”
Section: Resultsmentioning
confidence: 99%